Searching for Alternative Development of Economy and Marketing Role of Higher Economics Education in Russia - I. E. Belskikh; Yu. E. Golovina (Вестник Российского экономического университета имени Г. В. Плеханова)
Economy of the country and regions today find themselves in a complicated situation of choosing alternative ways of development. Declining international influence leads to analysis and substantiation of new ways of development. Marketing as a centre of coordination for region sustainable development is becoming a supporting structure for the growing appeal on home market. Higher economics education and its agents, i. e. Russian universities of economics will bear high responsibility for searching and substantiation of alternatives ways of working on markets. On the basis of expert assessment and comparative analysis of economics and other regional universities (pedagogical, technical, classical) competitive advantages of specialized higher education institutions in working with mass media were demonstrated. Managerial features, professional orientation of education and training programs, economic links with regional enterprises can highlight these advantages. Rising requirements of branch regulators to media activity of universities result in chaotization of information flows and increase in their impact on regional positioning. Therefore, we can observe an antagonistic dualism between harsh reality and magic virtual pictures. The authors put forward a logical scheme for resolving this problem, relying on synthesis of institutionalism, cluster approach (according to M. Porter) and conventional territorial and industrial marketing.